2014
DOI: 10.4336/2014.pfb.34.80.545
|View full text |Cite
|
Sign up to set email alerts
|

Resistência biológica da madeira tratada de duas espécies de Eucalyptus em ensaio de campo

Abstract: Resumo-A madeira, devido sua origem orgânica, dependendo das condições ambientais que seja exposta, pode ser deteriorada por agentes biológicos. Em vista disto, é extremamente importante que passe por algum tratamento preservativo, com o intuito de aumentar sua vida útil. A presente pesquisa teve por objetivo avaliar a resistência biológica de madeira tratada de Eucalyptus grandis e Eucalyptus cloeziana sob a ação de organismos biodeterioradores em ensaios de campo. Para tanto, foram utilizadas árvores de E. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
1
4
0
8
Order By: Relevance
“…The high reduction of mechanical features is related to the exposure environment, even if the wood has undergone preservative treatment. In similar work, Vivian et al (2014) found that samples set up in the forest deteriorated more than others did. These results relate to inherent edaphoclimatic characteristics of the forest environment that favor diversity and activity of decomposing wood organisms.…”
Section: Static Bendingmentioning
confidence: 85%
“…The high reduction of mechanical features is related to the exposure environment, even if the wood has undergone preservative treatment. In similar work, Vivian et al (2014) found that samples set up in the forest deteriorated more than others did. These results relate to inherent edaphoclimatic characteristics of the forest environment that favor diversity and activity of decomposing wood organisms.…”
Section: Static Bendingmentioning
confidence: 85%
“…Another aspect to be considered is the ecological characteristics of the site and the period in which the experiment was developed, besides the type of soil and the exposure site of the material near the water table are conditions that, according to Melo et al (2010), Vivian et al (2014) and Ribeiro et al (2014), favored soil saturation during the rainy season, also favoring anaerobic conditions for fungi action.…”
Section: /7mentioning
confidence: 99%
“…Avaliação 1 Resultados semelhantes de perda de massa foram verificados por diversos autores que avaliaram diferentes madeiras tratadas e não tratadas em ensaio de campo (MELO et al, 2010;ARAÚJO et al, 2012;CORASSA et al, 2013;MATTOS et al, 2013;VIVIAN et al, 2014). Não houve efeito significativo do material genético sobre o índice de deterioração e a perda de massa, tanto para as madeiras tratadas, quanto para as não tratadas.…”
Section: Materials Genéticounclassified
“…Espécies de Eucalyptus e Corymbia comumente são utilizadas no setor de biomassa da energia (EUFRADE JUNIOR et al, 2016) e papel e celulose (NEIVA et al, 2015). Tal destinação ocorre principalmente pelo mercado já estabelecido desses setores, além disso, essas espécies comumente apresentam baixa durabilidade natural, se mantendo em condições favoráveis de uso por poucos anos, quando em contato direto com o solo (VIDAL et al, 2015;VIVIAN et al, 2014;MAGA-LHÃES et al, 2012;ARAÚJO et al, 2012).…”
unclassified
See 1 more Smart Citation